2020
DOI: 10.1534/g3.120.401325
|View full text |Cite
|
Sign up to set email alerts
|

Adapting Genotyping-by-Sequencing and Variant Calling for Heterogeneous Stock Rats

Abstract: The heterogeneous stock (HS) is an outbred rat population derived from eight inbred rat strains. HS rats are ideally suited for genome wide association studies; however, only a few genotyping microarrays have ever been designed for rats and none of them are currently in production. To address the need for an efficient and cost effective method of genotyping HS rats, we have adapted genotype-by-sequencing (GBS) to obtain genotype information at large numbers of single nucleotide polymorphisms (SNPs). In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 72 publications
2
43
0
Order By: Relevance
“…To obtain genotypes, we used ddGBS, a genotyping method that reduces the complexity of the genome by only sequencing regions proximal to restriction enzyme cut sites [6,74]. We have recently described the technical aspects of this protocol in detail [75]. The ddGBS protocol used in this paper is a synthesis of the GBS approach described in Graboski et al [76] and used more recently by Parker et al [14] and Gonzales et al [33], and an analogous approach known as double digest restriction associated DNA sequencing (ddRADseq) [77].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain genotypes, we used ddGBS, a genotyping method that reduces the complexity of the genome by only sequencing regions proximal to restriction enzyme cut sites [6,74]. We have recently described the technical aspects of this protocol in detail [75]. The ddGBS protocol used in this paper is a synthesis of the GBS approach described in Graboski et al [76] and used more recently by Parker et al [14] and Gonzales et al [33], and an analogous approach known as double digest restriction associated DNA sequencing (ddRADseq) [77].…”
Section: Methodsmentioning
confidence: 99%
“…We have recently described the bioinformatic steps that we use for ddGBS in detail [75]. We follow an analogous approach in this paper, though we deviate at the imputation step due to our use of SD instead of HS rats.…”
Section: Methodsmentioning
confidence: 99%
“…Several recent studies found that standard NGS software is preferable to RAD-specific software in RADseq data analyses (Gileta et al, 2020;Shafer et al, 2017;Warmuth & Ellegren, 2019;Wickland et al, 2017). Warmuth and Ellegren (2019) showed that incorporating genotype uncertainty using ANGSD can improve demographic inference from RADseq data when compared to both a RADseq specific genotype calling pipeline, STACKS (Catchen et al, 2013;Rochette et al, 2019), and a widely used NGS genotype calling pipeline, GATK.…”
mentioning
confidence: 99%
“…This approach outperformed the RADseq specific software STACKS and TASSEL-GBS (Glaubitz et al, 2014). Finally, Gileta et al, (2020) showed that by mapping to a reference genome, genotype calling can be greatly improved with haplotype imputation from genotype likelihoods using ANGSD and Beagle (Browning & Yu, 2009) in combination. However, these three novel pipelines for RADseq data all assume that a reference genome is available, which is frequently not the case.…”
mentioning
confidence: 99%
“…Unfortunately, genome wide DNA variants have never been thoroughly uncovered in the NIH-HS rats. A recent study reported an adapted genotyping by sequencing (GBS) approach that was used to discover and genotype genome variants in this outbred strain [9,20]. No doubt, GBS is powerful, but this genome sampling sequencing approach may not reveal a comprehensive picture of DNA variants [21].…”
Section: Introductionmentioning
confidence: 99%